Bird community changes associated with cattle raising management in the delta forests of the Paraná River - Frutos, Antonio Esteban (2020)
Riparian forests and environments close to watercourses support high biodiversity, which may be modified by human activities. In the Paraná River Delta region, cattle raising is one of the activities with the greatest impact, altering vegetation structure. These changes are reflected in bird communities that inhabit these environments. We hypothesize that the absence of large herbivores (whether cows or native deer) will produce an increase in the vegetation cover of the lower strata of forests, due to the greater height of the herbaceous stratum and greater coverage of the shrub stratum, and that these changes mainly affect the species of birds that use resources associated with these strata. Our objective was to understand the changes in richness and abundance of the bird community among different types of cattle management using a functional aggregation approach of bird species. In the areas with cattle, we found less coverage of the shrub layer, lower height of the herbaceous layer and fewer climbing vines. We found that changes in richness and abundance of bird community were strongly related to species associated with the lower vegetation strata (ground-feeding guild, shrub guild and low canopy guild), and that the responses of the different guilds were not homogeneous. Understanding the direction of changes in bird communities occurring in response to modifications of the environment, allows us to optimize conservation efforts. If these efforts are based on conservation of the environment in its natural state, we should adjust the management of the herbivory to the pristine conditions of the environment. On the other hand, if conservation efforts are based on particular species or groups of species associated with certain resources, the correct management of herbivory by cattle can be essential to obtain successful results.